Intervertebral Disc Degeneration Mediates the Causal Effect of Genetically Predicted Diffuse Idiopathic Skeletal Hyperostosis on Spinal Stenosis: Evidence From a Mendelian Randomization Study - Yanzhu Shen; Yankun Jiang; Ruichen Jiang; Yanjun Huang; Sizheng Zhan; Yuming Wang; Xiangsheng Tang; Ping Yi (JOR Spine)
ABSTRACT Background Previous studies have noted an association between diffuse idiopathic skeletal hyperostosis (DISH) and spinal stenosis (SS), although causation is unclear. This study used Mendelian randomization (MR) to investigate the causal relationship between the two. Methods We utilized large GWAS datasets on DISH and SS to perform a two‐sample, bidirectional MR analysis, also quantifying the mediating role of intervertebral disc degeneration (IDD). The inverse variance weighting (IVW) method was the primary approach used to estimate the causal effect size. To ensure the reliability of MR results, we conducted heterogeneity tests, horizontal pleiotropy tests, and the MR‐PRESSO test. Results The random‐effects IVW method indicated that genetically predicted DISH was associated with an increased risk of SS (OR: 1.432; 95% CI: 1.097–1.868; p = 0.008), and this association remained significant in the validation dataset (OR: 1.444; 95% CI: 1.208–1.725; p < 0.001). Mediation analysis in homogeneous populations showed that IDD partially mediates the causal effect of DISH on SS, with a mediation ratio of 38.39% (95% CI: 2.66–74.13). Sensitivity analyses supported our conclusions. Conclusions This study provides causal evidence that genetically determined DISH is associated with an increased risk of SS, with IDD acting as a partial mediator. These findings underscore the importance of spine‐protective behaviors and early IDD prevention strategies in patients with DISH to mitigate SS risk.